Odcieleśnione ciało w filmie Nakarmić kruki Carlosa Saury - Kulessa , Kamila (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
This article aims at providing an analysis of Carlos Saura’s Cria Cuervos [Raise ravens, 1976], focused mainly on the temporal and spatial structures of the film. It explores the dimensions of bodily presence, especially the means of representing spectral body in cinematic image.